Iron Sucrose Versus Oral Iron Therapy in Pregnancy Anemia - Syal Neeru; N Sreekumaran Nair; Lavanya Rai (Wolters Kluwer Medknow Publications, 2012)
Background: Iron deficiency anemia (IDA) is the most common medical problem in pregnancy. Parenteral iron is a useful treatment, although iron dextran use decreased due to anaphylaxis. Iron sucrose is a newer agent that has overcome the shortcomings of iron dextran. Objective: The aim of this study was to compare the efficacy and tolerance of intravenous iron sucrose (IVIS) therapy with oral iron (OI) therapy in pregnant women with IDA and to study the factors influencing treatment. Materials and Methods: This prospective, randomized clinical trial included pregnant women between 14 and 36 weeks with established IDA who were treated with IVIS or OI (ferrous fumarate). All patients were monitored for laboratory response and adverse effects. Independent sample-t test, Chi square test and ANOVA were used for statistical analysis. P < 0.05 was considered significant. Results: Although hemoglobin increased in both the groups, increase in the reticulocyte count and percentage increase in hemoglobin was significantly higher in the IVIS group than in the OI group (23.62% vs. 14.11%). Serum ferritin was significantly higher in the IVIS group than in the OI group (P = 0.000). The IVIS group had no major side-effects. Compliance was good with OI, although 23% had gastrointestinal side-effects. Patient weight, gestation at diagnosis, initial hemoglobin and ferritin levels did not influence the response to treatment. Conclusion: IVIS is safe and effective in the treatment of IDA during pregnancy. Iron stores increased better with IVIS compared with OI.